Management of acute exacerbations of asthma - Fanta, Chris (Henry Stewart Talks, 2013)
Asthma prevention, assessment, treatment and disposition, Risk factors and physical findings in severe asthma attacks, Treatments: Steroids, MDI, Nebulizer, Beta-agonists, Bronchodilators, Magnesium, Heliox & Antibiotics, Unproven and unconventional therapies, Rationale for in-hospital treatment and indications for admission, Indications for intubation & mechanical ventilation, Discharge criteria and patient education prior to hospital discharge